Metagenomics Basics, Methods and Applications - Hozzein, Wael N. (IntechOpen, 2020)
This book is for the students starting their research projects in the field of metagenomics, for researchers interested in the new developments and applications in this field; and for teachers involved in teaching this subject. The book is divided into three sections as indicated from its title, namely; the basics of metagenomics, metagenomic analysis, and applications of metagenomics. It covers the basics of metagenomics from its history and background, to the analysis of metagenomic data as well as its recent applications in different fields. The book contains excellent texts at both the introductory and advanced levels, that describe the latest metagenomic approaches and applications, from sampling to data analysis for taxonomic, environmental, and medical studies. Finally, the publication of this book was an interesting journey for me and I hope the readers will enjoy reading it.